2011
DOI: 10.5812/kowsar.22287523.2130
|View full text |Cite
|
Sign up to set email alerts
|

Use of Remifentanil and Alfentanil in Endotracheal Intubation: A Comparative Study

Abstract: Background:Opioids, such as alfentanil, are used to facilitate endotracheal intubation without the use of neuromuscular blocking agents in patients undergoing elective surgery.Objectives:The goal of this study was to evaluate the endotracheal intubation conditions when remifentanil or alfentanil was used with propofol without the application of neuromuscular blocking agents.Patients and Methods:One hundred American Society of Anesthesiologists (ASA) grade I patients scheduled for elective surgery were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…We read with great interest the article, "Use of Remifentanil and Alfentanil in Endotracheal Intubation: A Comparative Study," by Imani et al (1). The authors demonstrated that remifentanil in combination with propofol provides excellent conditions for endotracheal intubation in young, healthy patients to avoid the use of muscle relaxants.…”
Section: Dear Editormentioning
confidence: 95%
“…We read with great interest the article, "Use of Remifentanil and Alfentanil in Endotracheal Intubation: A Comparative Study," by Imani et al (1). The authors demonstrated that remifentanil in combination with propofol provides excellent conditions for endotracheal intubation in young, healthy patients to avoid the use of muscle relaxants.…”
Section: Dear Editormentioning
confidence: 95%
“…I read the paper by Imani et al (1) with interest and must congratulate them in attempting to show the advantages of administering remifentanil for laryngoscopy and tracheal intubation in adult patients. It was interesting to know the experiences of colleagues with regard to tracheal intubation in noncardiac patients, as I use a combination of remifentanil and propofol in my daily practice in cardiac anesthesia.…”
Section: Dear Editormentioning
confidence: 99%
“…Remifentanil is 20 to 30 times more potent than alfentanil and its elimination half life is 3.8-8.3 minutes. Compared to alfentanil, remifentanil's effect reduces much more quickly after intubation; this is an important advantage over alfentanil, especially in short-term and outpatient surgeries (1,3,6).…”
mentioning
confidence: 99%
“…In a related study, Mohammadreza et al (9) In a related study, Imani et al (1) reported better intubation conditions with the combination of 5 µg/kg of remifentanil with 2 mg/kg of propofol than with 2 mg/kg of propofol, 50 µg/kg alfentanil, and 5 µg/kg of remifentanil. Nonhomogeneous distribution of doses, administration speed of agents, injection durations, time elapsed between injection and intubation, different scoring systems used for evaluation of intubation conditions, and age intervals of the cases enrolled in the studies all lead to difficulties in comparing these studies (1,(6)(7)(8)(9)(10). Some limitations are also present with Imani et al's study.…”
mentioning
confidence: 99%
See 1 more Smart Citation